ChatGPT's Validity and Reliability in Islamic Legal Studies: A Critical Assessment of Waqf for Early Learners - Susanti, Neng Fitri Hedi; Tanjung, Hendri; Supriyanto , Trisiladi; Athief, Fauzul Hanif Noor; Furqoni, Aminullah (Universitas Muhammadiyah Surakarta, 2025)
This study evaluates the validity and reliability of ChatGPT in presenting Islamic legal knowledge on waqf, focusing on its usefulness for early learners relying on free digital tools without formal Islamic education. Conducted in Indonesia, the world’s largest Muslim-majority country, the research uses ChatGPT-3.5 in Indonesian. Data were analyzed qualitatively by comparing ChatGPT’s responses with Al-Mawsūʿah al-Fiqhiyyah al-Kuwaitiyyah, Buku Pintar Wakaf, and Buku Wakaf Kontemporer across four dimensions: basic concepts, pillars and conditions, nazir (trustee) aspects, and contemporary issues. Each was rated on a five-point scale. ChatGPT scored highest in basic concepts (validity 4.80, adequacy 4.60), followed by pillars and conditions (4.44; 4.06) and Nazir (4.23; 4.06). The lowest performance was in contemporary issues (3.57 for both). Findings indicate that ChatGPT provides an accurate foundational understanding but lacks sufficient legal depth and contextual precision for advanced study. Thus, it should serve as a supplementary learning aid, not a substitute for scholarly guidance, authoritative references, or structured Islamic education grounded in sanad.